Analisis Kinerja Keuangan Dengan Pendekatan Maqashid Syariah Index Pada Perbankan Syariah Indonesia dan Malaysia - Dita Andraeny; Nur Rina Aminati (Institut Agama Islam Negeri Madura, 2024)
This study was conducted on the grounds that the measurement of financial performance of Islamic Commercial Banks (BUS) still uses measurements from conventional banks. This study aims to analyse and compare the performance of Islamic banking in Indonesia and Malaysia using the Maqashid Syariah Index (MSI) approach. Quantitative descriptive method with secondary data using annual reports and financial statements of each Islamic bank. The research objects were 14 Indonesian BUSs and 15 Malaysian BUSs that published financial reports in 2020. The steps taken to measure the financial performance of Islamic banks using the Maqashid Syariah Index (MSI) are performance ratio assessment, performance indicator assessment and finally MSI assessment and weighting. The results of the study concluded that there were differences in financial performance based on the MSI value between Indonesian and Malaysian BUSs. BUS performance in Indonesia is considered better in achieving maqashid sharia compared to BUS in Malaysia. The measurement results prove that Bank Jabar Banten Syariah is the Indonesian BUS that gets the highest maqashid sharia value. Meanwhile, the highest value Malaysian BUS is AmBank Islamic Berhad.